Automatic Evaluation for E-Learning Using Latent Semantic Analysis: A Use Case - Farrús, Mireia; R. Costa-jussà, Marta (International Review of Research in Open and Distributed Learning, 2013)
Assessment in education allows for obtaining, organizing and presenting information about how much and how well the student is learning. The current paper aims at analysing and discussing some of the most state-of-the-art assessment systems in education. Later, this work presents a specific use case developed for the Universitat Oberta de Catalunya, which is an on-line University. An automatic evaluation tool is proposed so that it allows the student to evaluate himself anytime and receive instant feedback. This tool is a web-based platform and it has been designed for engineering subjects (i.e. with math symbols and formulas) in Catalan and Spanish. Particularly, the technique used for automatic assessment is Latent Semantic Analysis. Although the experimental framework from the use case is quite challenging, results are promising.